OPTIMALISASI PENGELOLAAN BADAN USAHA MILIK DESA TERHADAP KESEJAHTERAAN MASYARAKAT DESA BULO - Kiki Syani; Kamaruddin Sellang; Ahmad Mannu (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
Optimizing the Management of Village-Owned Enterprises for Community Welfare in Bulo Village, Panca Rijang District, Sidenreng Regency. Rappang is what this essay is intended to explain. According to this study's population estimates, there are 2,530 people living in Desa Bulo, a village in the Panca Rijang district of Sidenreng Rappang, who were sampled using rumors Slovin and a non-probability sampling technique. This type of research paper is a quantitative descriptive. The data collection techniques used in this study are observation, questionnaire, interview, and documentation. The data analysis methodology used is the standalone version of IBM SPSS Statistics 21.0. The results of this study indicate that the optimizationi Management Village-Owned Enterprises Against Community Welfare in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency. Based on the results of the recapitulation of the Governance variable, it is in the poor category with a percentage of 56%. Community Welfare with a percentage of 49.9% is in the poor category. Optimizing the management of village-owned enterprises